LEARNING STYLES AND TEACHING STYLES. A MODEL OF CATEGORIZATION OF STUDENTS’ LEARNING STYLES FROM TEACHERS’ PERSPECTIVE - López García, Juan Manuel (Anales de Psicología / Annals of Psychology)
The goal of the present work is to obtain different students’ categories. These are made by the combination of four variables: intelligence, motivation, learning skills and positive study habits. These categories were obtained through teachers’ observations of secondary education students. Only the combination of these four variables which were compatible and viable in the classroom were used to get a pupil tipology. This tipology is intended to be exhaustive. This tipology doesn’t analyse other factors that can influence the students’ learning styles and that are not directly related to the four variables mentioned above. A second goal is to attribute an appropriate teaching strategy to each student’s category. It is an initiative directed to increase the quality of teaching and it is related to the attention to diversity.